The Effectiveness of the Use of Project-Based Learning Strategies in Learning to Write Essay Texts Containing Archipelago and Maritime Insights in Grade XII Students of SMAN Taruna Nala Malang - Nurul Khisbiyah; Didin Widyartono; Karkono Karkono (Eduvest - Journal of Universal Studies, 2025)
This study measures the effectiveness of the use of project-based learning strategies for learning to write essay texts that contain archipelago and maritime insights in grade XII students of SMAN Taruna Nala Malang. The low writing skills among students are the background of this study because students experience difficulties in organizing their minds and developing essay frameworks and have limited vocabulary. Students can increase creativity and independence as well as responsibility and confidence and critical thinking skills because project-based learning strategies are chosen. This study uses an experimental method and uses a one group pretest-posttest design. A total of 22 students in grades XII-4 of SMAN Taruna Nala Malang participated in the research. The results of the study showed a significant improvement in students' writing skills after the implementation of this strategy, with an average increase in pretest and posttest scores of 18.15. The normality test showed normal distributed data, and the t-test showed a significance of 0.02 < 0.05, meaning that there was a significant influence from the implementation of the chosen strategy. The effectiveness of this strategy is included in the medium category with an average n-gain value of 0.419. This study proves that project-based learning strategies are effective in improving essay writing skills with archipelago and maritime insights.